Rectus Femoris-based Muscle Pedicle Bone Graft for Osteonecrosis of Femoral Head: A New Surgical Technique. Issue 4 (December 2021) - Krishna, Anant; Kumar, Manoj; Yadav, Rajeev; Mehta, Rohan; Arora, Sumit
Abstract : The pre-collapse and pre-degenerative stages of osteonecrosis of femoral head in young adults are preferably treated by a femoral head preservation operation with the objective to delay or possibly avert the further necrosis, collapse and degeneration of the hip joint. To salvage the early stages of the disease, several muscle pedicle bone grafting (MPBG) procedures based on Quadratus Femoris, Tensor Fasciae Latae, and Sartorius muscles have been described in the literature. To overcome the limitations of these procedures, the authors describe here a much simpler and safer MPBG based on the straight head of the Rectus Femoris with distal transposition of its origin along with anterior inferior iliac spineto the head-neck junction. To the best of our knowledge, MPBG based on Rectus Femoris has not been reported in the currently available literature on osteonecrosis of femoral head. Surgical technique with emphasis on protection of the posterior retinacular vessels, post-operative care and expected outcome is presented.